Non-invasive and reliable assessment of compartment elasticity by pressure related ultrasound: An in-vitro study. Issue 4 (April 2021) - Sellei, R.M.; Warkotsch, U.; Kobbe, P.; Weber, C.D.; Reinhardt, N.; de la Fuente, M.; Radermacher, K.; Hildebrand, F.
Highlights: Non-invasive measurement of muscle elasticity as surrogate of invasive pressure measurement. Highly Reliable approach for monitoring muscle elasticity by ultrasound. High correlation between the increasing intra-compartmental pressure and decreasing elasticity. Abstract: Purpose: The development of acute compartment syndrome is a serious threat to trauma patients. The clinical assessment alone is not reliable enough to determine the need for fasciotomy in many cases. The Physician´s assessment of the elasticity of the muscle compartment might be particularly important to objectively evaluate the pressure in this enclosed space. The purpose of this study was to determine the observer´s reproducibility, of compartment elasticity measurements by a novel ultrasonic approach. Methods: Increasing intra-compartmental pressures (ICP) were simulated in a water filled in-vitro model. Pressure related ultrasound was used to determine the relative elasticity (RE) of soft tissue compartments. A pressure transducing probe head was combined with the ultrasonic probe to obtain cross section views of the simulated compartment and to detect the amount of applied pressure by the observer. In this model, the compartment depth without compression (P0 ) was set to be 100%. Changes of the compartment depth due to a probe pressure of 80 mmHg (P80 ) were correlated to P0 and an elasticity quotient as a value for RE (%) was calculated. Twelve blinded observers performed measurements for RE determination (%) under three pressure conditions. Reproducibility was calculated using intraclass correlation coefficient (ICC). Results: Measurements ( n = 432) revealed that the RE (%) in the control group was 17, 06% (SD+/-2, 13), whereas the RE of the group ICP30 significantly decreased to 12, 66% (SD+/- 1, 19) ( p <0, 001). The ICP50 group revealed a further significant decrease to 8, 43% (SD+/- 0, 67) ( p <0, 001). Repeated measurement of RE and ICP showed a high level of correlation (spearman correlation coefficient: roh=0, 922). A RE <14% resulted in a sensitivity of 96% and a specificity of 90, 3% for diagnosis of an ICP >30 mmHg. ICCinter was 0, 986; 95%, CI: 0, 977–0, 992 ( p <0, 001). Discussion: The presented ultrasound-based approach reliably assesses the elasticity in a simulated compartment model. In this pioneer study investigating the inter- and intra-observer reproducibility, this method of measurement appears to be of low cost in addition to being an easy and secure approach that may have the potential to substitute invasive measurement. Further investigations are required to improve its feasibility and to confirm the reliability under clinical conditions.